UZBEK-CHINESE RELATIONS ON THE WAY OF IMPLEMENTING A CONSISTENT, PEACE-LOVING CONSTITUTIONAL POLICY OF THE COUNTRY - Usmanov , Sardorbek Abdullayevich (Educational Research in Universal Sciences, 2023)
The article highlights the prospects for cooperation between Uzbekistan and China, aimed at developing trade, economic and investment relations in the context of constitutional reforms. Priority is given to infrastructure projects to expand new export markets. Guidelines for the development of bilateral relations in the fields of energy, industry, transport, innovation, green and digital economy are presented, as well as experience in diversifying the infrastructure network and expanding new export markets. Attention was focused on the exchange of experience in the field of culture, education, healthcare, tourism, sports and other areas of mutual interest, friendly contacts between the media, scientific and educational institutions, and artistic groups of the two countries.